2016
DOI: 10.1007/jhep05(2016)075
|View full text |Cite
|
Sign up to set email alerts
|

Conformal blocks beyond the semi-classical limit

Abstract: Black hole microstates and their approximate thermodynamic properties can be studied using heavy-light correlation functions in AdS/CFT. Universal features of these correlators can be extracted from the Virasoro conformal blocks in CFT 2 , which encapsulate quantum gravitational effects in AdS 3 . At infinite central charge c, the Virasoro vacuum block provides an avatar of the black hole information paradox in the form of periodic Euclidean-time singularities that must be resolved at finite c.We compute Viras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
149
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(161 citation statements)
references
References 60 publications
10
149
0
Order By: Relevance
“…In a very nice set of papers, the existence of gravitational redshift was shown in the CFT [34][35][36][37][38]. The basic idea was to look at the identity conformal block; this corresponds to exchange of the stress tensor in the CFT, which corresponds to exchanging a graviton in the gravity description.…”
Section: Finding Redshift In Gravitymentioning
confidence: 99%
See 1 more Smart Citation
“…In a very nice set of papers, the existence of gravitational redshift was shown in the CFT [34][35][36][37][38]. The basic idea was to look at the identity conformal block; this corresponds to exchange of the stress tensor in the CFT, which corresponds to exchanging a graviton in the gravity description.…”
Section: Finding Redshift In Gravitymentioning
confidence: 99%
“…In [41] an explicit model of shell collapse was studied, using the methods of [34][35][36][37]. The shell was represented by a number of infalling particles in the gravity description, and a…”
Section: Finding Redshift In Gravitymentioning
confidence: 99%
“…It would be interesting to generalize our results to black-hole-like extremal solutions where one allows also singularities of parabolic or hyperbolic type. 10 • It would be interesting to generalize our results to 3D higher spin gravity, relating multi-centered higher spin solutions to W -algebra conformal blocks [55]. Since massless higher spin fields are most simply formulated in terms of Chern-Simons fields, this would involve a generalization of the Chern-Simons description of our solutions discussed at the end of section 4.…”
Section: Jhep03(2017)129mentioning
confidence: 99%
“…Recent investigations have focused on the important question of how local physics in the bulk is encoded in properties of the dual CFT. Natural localized objects to study holographically are line defects arising from adding point particles to the bulk, which have recently been shown to be intimately linked to conformal blocks in the dual CFT [2][3][4][5] (related work appears in [6][7][8][9][10][11][12][13][14][15][16][17]). In the case of AdS 3 , which we will focus on in this paper, it was shown that Virasoro conformal blocks at large central charge can be computed from the action of configurations of point particles in the bulk AdS 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The essence is that the presence of the heavy operators change the background geometry to a BTZ black hole. For other aspects on this type of conformal block, see [27][28][29][30][31].…”
Section: Jhep10(2016)110mentioning
confidence: 99%